Suture in esophageal surgery - Balboa, Oscar; Sarroca, Carlos; Morelli, Raúl; Tchekmedyian, Vartan; Geninazzi, Héctor; Ricciardi, Norma; Praderi, Luis A (Cirugía del Uruguay, 1983)
The experience in 21 patients in which esophageal sutures using an anastomoticlstapling device were performed, is presented, analyzing sorne technical aspects. The development of stenosis rela ted to the use of small caliber machines and the low frequency of anastomotic Ieakages are showed. The usefulness of the procedure is concluded.